Diversity, Ecology and Distribution of Indian Lactuceae (Asteraceae) - Mamgain, S. K. (Indian Forester, 1999)
The present communication deals with diversity, ecology and distribution of Indian Lactuceae (Asteraceae) which is represented by 10 genera namely Lactuca L., Prenanthes L., Launaea Cass., Sonchus L., Reichardia Roth, Cicerbita Wallr., Ixeris, Cass., Chondrilla L., Dubyaea DC and Youngia Cass., with 80 taxa in India. Among these 9 genera and 51 taxa are from the Western Himalaya, 7 genera and 31 taxa from Eastern Himalaya, 5 genera and 12 taxa from Western and Eastern Ghats and 6 genera and 15 taxa from Gangetic plains, Rajasthan and other parts of the country. The Lactuceae exhibit wide range of variations in its ecological habitats from sea coast to 5000 m in elevations and exhibit enormous diversity both intraspecifically and interspecifically. The Himalayas are shown to be major centre for Lactuceae diversity and distribution followed by Western Ghats and Gangetic plains. At generic level Lactuca exhibits maximum diversity with 25 species followed by Youngia and Cicerbita, all three are predominantly Himalayan. The genus Dubyaea is endemic to Sino-Himalayan region with 9 species, while 6 of its 9 species are highly localized in this region. The maximum diversity of Lactuceae in the Himalaya is due to a variety of climatic conditions and altitudes which in turn has resulted in diverse habitats. The Lactuceae inhabit every conceivable habitats and reveals a great amount of variation in the populations of different species. The distribution analysis of Lactuceae reveals that its members are chiefly distributed in the Himalaya and poorly represented in Western Ghats, Eastern Ghats and Gangetic plains.